Incidence of metopism in dried skulls of adults from the osteological collection of the faculty of medicine of FAP-Araripina (PE) - Lima, Larissa Luana Lopes; Oliveira, Regina Moura de; Santos, Ana Hester Silva; Freires, Maria Eduarda Gomes; Simião, Jonatas Monteiro; Neto, Alexandrino José de Carvalho; Júnior, Erasmo de Almeida; Ferreira, Émerson de Oliveira (Seven Editora, 2023)
During fetal life and childhood, the bones of the skull and face are separated by dense connective tissue membranes with large amounts of collagen fibers that constitute the sutures. One of these is the metopic suture, which joins the two frontal bones in the embryonic period and in the newborn. This suture appears approximately at the end of the second month of intrauterine life between the two ossification centers of the frontal bone, being considered as an anterior extension of the sagittal suture and its total fusion can occur from the end of the first year to the eighth or tenth year of life. , and may persist in adults. The objective of our study was to verify the incidence of metopic suture in dry skulls of adults in the Northeast region of Brazil. A sample of 474 dry skulls of adults, 294 male and 180 female, belonging to the Forensic Anthropology Center of the Faculty of Medicine of FAP-Araripina was used. In general, 84.6% of the skulls did not have a persistent metopic suture, with 3.6% having a complete metopic suture, 10.3% an incomplete metopic suture of the nasion type and 1.5% an incomplete metopic suture of the nasion type. bregma type. Complete metopic suture was more frequent in males (2.3%) than in females (1.3%). Due to the large territorial extension of Brazil and the great miscegenation of the population, in our view, it is necessary to carry out more studies in Brazilian individuals through dry skulls or images, especially if carried out in different regions of our country. DOI:https://doi.org/10.56238/sevened2023.004-018